Explanation:
Hey,there!!!
Let's simply work with it,
We have,
One point is (x2,y2) and midpoint is(x,y).
Now, let's use midpoint formulae,
![(x ,\: y) = (x1 + x2)/(2) + (y1 + y2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/xkipxawqc08z6wqr3ejvbs4a9tjvv3mtx5.png)
Now, let's equate with their corresponding elements we get,
![x = (x1 + x2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ivfsmglw5qzxg7kang5sgpon79irk7qr4g.png)
now, 2x=x1+x2
or, x1=2x-x2
and
![y = (y1 + y2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/60grd99a183wp9k9bf1k6khcex89aznl7u.png)
now,
2y = y1+y2
or, y1 = 2y-y2
Therefore, the answer is (x1,y1)= { (2x-x2),(2y-y2) }
Hope it helps...